Análisis morfológico y técnico de ventanas y su relación con el confort térmico y lumínico : caso de estudio: apartamento VIS en Bogotá (2017)
"The purpose of this investigation was to demonstrate how, by applying simple passive design strategies focused on the building?s windows and faÅades in relation to solar radiation, is possible to establish ideal comfort levels in illumination and thermal conditions in an apartment (case study) of Low Income Housing, located in the savanna of Bogota. Versus installing a costly heating system. The results were achieved by performing a number of hypothetical energy efficiency simulations with DesignBuilder and EnergyPlus (energy simulation programs), applying variations in faÅade orientations, window to wall ratio and wall depth." -- Tomado del Formato de Documento de Grado.